Efektivitas Terapi Eft (Emotional Freedom Technique) Terhadap Manajemen Stres Perawat Di Rs Marzoeki Mahdi: The Effectiveness of EFT (Emotional Freedom Technique) Therapy on Stress Management Among Nurses at Marzoeki Mahdi Hospital - Andira Eka Wardani Eka; Arif Hidayatullah; Rina Afrina (Journal of Nursing Education and Practice, 2026)
Introduction: Occupational stress is a major issue among nurses, especially in psychiatric hospitals, due to high emotional demands, workload, and intensive patient interactions. Unmanaged stress can reduce nurses’ performance and healthcare quality. Emotional Freedom Technique (EFT) is a promising non-pharmacological intervention. Objectives: To examine the effectiveness of Emotional Freedom Technique (EFT) on stress management among nurses at Marzoeki Mahdi Psychiatric Hospital. Method: Participants were selected using purposive sampling. A quasi-experimental pre-test and post-test design with a control group was conducted among 36 nurses. The intervention group received EFT therapy for seven days, while the control group received stress management education. Stress levels were measured using the Expanded Nursing Stress Scale (ENSS). Data were analyzed using Wilcoxon and Mann–Whitney tests. Result: Stress levels significantly decreased in the intervention group after EFT therapy (p < 0.001). There was a significant difference in post-test stress levels between the intervention and control groups (p = 0.044). Conclusion: EFT is effective in reducing nurses’ stress levels and can be recommended as a non-pharmacological stress management intervention in psychiatric hospitals.